Key Factors In Character Education - Agnes Renostini Harefa; Nathanael Sitanggang (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study successfully identified key factors in character education, involving 34 variables assumed to have a strong correlation with character values. The testing was conducted through various methods, including the Kaiser Meyer Olkin (KMO) test, Bartlett's test, MSA, and confirmation of eigenvalues greater than 1, as well as based on the emerging factor loadings. This research uses explanatory factor analysis to identify key character factors that influence the successful implementation of character education at SMK Negeri 1 Gunungsitoli. This type of research is applied research that applies explanatory factor analysis methods. data obtained by carrying out the dissemination of quesioner to respondents, namely students of SMK State 1 Gunungsitoli of 60 students. The factor analysis results revealed that out of 43 variables, eight main factors were identified to explain the key aspects of character education. The first factor encompasses the ethics and personality of students, while the second factor involves the ethics and discipline of students. The third factor highlights the obedience and communication of students, while the fourth factor focuses on social ethics and student involvement. The fifth factor includes self-ethics and social interaction among students, while the sixth factor is related to academic ethics and the discipline of student learning. The seventh factor emphasises honesty and communication among students, and the eighth factor involves team collaboration and student participation.